Testosterone therapy and venous thromboembolism: A systematic review and meta-analysis. Issue 172 (December 2018) - Houghton, Damon E.; Alsawas, Mouaz; Barrioneuvo, Patricia; Tello, Mouaffaa; Farah, Wigdan; Beuschel, Brad; Prokop, Larry J.; Layton, J. Bradley; Murad, M. Hassan; Moll, Stephan
Abstract: Background: Testosterone prescribing for men has dramatically increased, and there have been concerns about inappropriate use and adverse events. While regulatory bodies have warned about increased risk of venous thromboembolism (VTE), published clinical data supporting an increased risk for VTE are limited. Objective: To conduct a systematic review of studies examining the association between testosterone therapy in men and VTE. Methods: Comprehensive searches of multiple databases were performed from inception through October 3rd, 2018. Randomized control trials (RCTs) and observational studies examining the association between exogenous testosterone (any route) and VTE. Study selection and data extraction were performed by two independent investigators. Random-effect model meta-analyses were used to estimate pooled odds ratios (OR) and 95% confidence intervals (CIs). Heterogeneity among studies was evaluated using the I 2 statistic. Risk of bias was assessed using the Cochrane and Newcastle-Ottawa tools. Results: Six RCTs ( n  = 2236) and 5 observational studies ( n  = 1, 249, 640) were included. Five RCTs were performed in men with documented hypogonadism. The observational studies included: 2 case-control studies, 2 retrospective cohorts, and 1 retrospective cohort with a nested case-control study. There was no evidence of a statistically significant association between VTE and testosterone (OR 1.41, 95%CI 0.96–2.07). Heterogeneity was high (I-squared = 84.4%). The association remained nonsignificant when the analysis was stratified by study design: RCTs (2.05, 95% CI 0.78–5.39); cohort (1.06, 95% CI 0.85–1.33); and case-control (1.34, 95% CI 0.78–2.28). The overall risk of bias was moderate. Conclusions: The current evidence is of low certainty but does not support an association between testosterone use and VTE in men. Highlights: The Food and Drug Administration warns against VTE in testosterone users. 6 RCTs and 5 observational studies examining testosterone and VTE are reviewed. No significant association was found between testosterone and VTE. Limited data from RCTs and heterogeneity in observational studies limit conclusions. We conclude our review with 8 summarizing clinical management considerations.